2021
DOI: 10.1590/1678-7757-2021-0383
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of single and repeated sessions of photobiomodulation with two different therapeutic wavelengths for reducing postoperative sequelae after impacted mandibular third molar surgery: a randomized, double-blind clinical study

Abstract: The effects of the number of photobiomodulation (PBM) sessions on the postoperative inflammatory process remain controversial. The current literature comparing single and repeated PBM sessions is limited. Objective This study aimed to compare the effects of single and repeated PBM sessions, applied at two different therapeutic wavelengths within the infrared spectrum, on postoperative inflammatory response after impacted third molar tooth extraction. Methodology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In a recent randomized clinical trial, the single-session and repeated-session protocols were compared. It was found that there was no difference between the two protocols, and the single-session protocol was recommended [40].…”
Section: Discussionmentioning
confidence: 98%
“…In a recent randomized clinical trial, the single-session and repeated-session protocols were compared. It was found that there was no difference between the two protocols, and the single-session protocol was recommended [40].…”
Section: Discussionmentioning
confidence: 98%
“…Postoperative trismus assessment — Spasms in the masticatory muscles (trismus) can limit or even prevent mouth opening after the surgical removal of impacted third molars [ 21 , 23 , 29 ]. This outcome is typically evaluated by measuring the distance between the incisal edges of the upper and lower central incisors using calipers [ 27 , 29 ]. In this study, previously calibrated evaluators will measure mouth opening in each patient before surgery as well as two and seven days after surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Postoperative trismus assessment-Spasms in the masticatory muscles (trismus) can limit or even prevent mouth opening after the surgical removal of impacted third molars [21,23,29]. This outcome is typically evaluated by measuring the distance between the incisal edges of the upper and lower central incisors using calipers [27,29].…”
Section: Plos Onementioning
confidence: 99%
“…[25][26][27][28][29] Four studies were excluded due to various reasons (Table 1). [30][31][32][33] The study selection procedure was done by two independent reviewers (SG and AD) and any disagreements between the reviewers were solved by discussion. The study selection procedure is shown in (Figure 1).…”
Section: Study Selectionmentioning
confidence: 99%